MAKNA PASKAH YAHUDI DALAM HUBUNGANNYA DENGAN PASKAH KRISTEN MENURUT KITAB KELUARAN 12:1-12 - Modeong, Claudio; Umar, Denny; Pinontoan, Raphael; Warouw, Agung; Kasiahe, Evi Martika (Pineleng Theological Review, 2024)
This article explored the theological and symbolic relationship between Jewish and Christian Passover. Both celebrations is rooted in different traditions, yet deeply interconnected. Based on Exodus 12:1-28, Jewish Passover (Pesach) commemorates the freedom of the Israelites from slavery in Egypt through the ritual of slaughtering an unblemished lamb and applying its blood to the doorposts, symbolizing God's protection and salvation. This celebration also involves the consumption of unleavened bread and bitter herbs, representing the suffering and haste of their escape from Egypt. In Christian tradition, Easter is understood as the celebration of the resurrection of Jesus Christ, believed to fulfill the meaning of Jewish Passover. Jesus, as the Lamb of God, sacrificed Himself to redeem humanity's sins. By studying these two celebrations, this article aims to deepen the understanding.